OPTIONS for Preparing Inmates for Community Reentry: An Employment Preparation Intervention Ψ. (October 2013) - Fitzgerald, Erica L.; Chronister, Krista M.; Forrest, Linda; Brown, Lindsey
The purpose of this study was to adapt and experimentally test the effectiveness of a research-based, employment-focused group counseling intervention (OPTIONS). OPTIONS was designed to increase male inmates' exploration and identification of employment interests and options, identification and development of employment-search skills, and knowledge of vocational options, goal planning, and identification and use of contextual supports. A randomized block design and measurements at pretest, posttest, and 1-month follow-up were used to examine the effects of OPTIONS. Participants included 77 ( n = 38 treatment, n = 39 control) adult male inmates. Results indicated that OPTIONS participants had higher career search self-efficacy, problem solving, and hopefulness scores at posttest and follow-up than did treatment-as-usual control group participants.